2010
DOI: 10.1109/tuffc.2010.1523
|View full text |Cite
|
Sign up to set email alerts
|

Laser ultrasonic inspection of plates using zero-group velocity lamb modes

Abstract: A noncontact laser-based ultrasonic technique is proposed for detecting small plate thickness variations caused by corrosion and adhesive disbond between two plates. The method exploits the resonance at the minimum frequency of the S(1) Lamb mode dispersion curve. At this minimum frequency, the group velocity vanishes, whereas the phase velocity remains finite. The energy deposited by the laser pulse generates a local resonance of the plate. This vibration is detected at the same point by an optical interferom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 25 publications
1
25
0
2
Order By: Relevance
“…Additionally the numerical investigation includes the effect associated with the plate thickness variation from to 2 . As it was reported previously in literature [7,16], the ZGV frequency exhibits a linear behavior with respect to ( −1/2 ).…”
Section: Influence Of Shear Modulus On the S 1 -Zgv Frequencysupporting
confidence: 82%
See 2 more Smart Citations
“…Additionally the numerical investigation includes the effect associated with the plate thickness variation from to 2 . As it was reported previously in literature [7,16], the ZGV frequency exhibits a linear behavior with respect to ( −1/2 ).…”
Section: Influence Of Shear Modulus On the S 1 -Zgv Frequencysupporting
confidence: 82%
“…To exploit this phenomenon recent works evoke the idea that it may be suitable for the measurement of nanometer-scale thickness variations in homogeneous plates [6,7]. Due to the resulting differential equations of variable coefficients associated with the spatial variation of the material properties, the wave propagation in FGM remains difficult to analyze.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequency dependency of the reflection coefficient revealed the thickness and elastic properties of the adhesive layer. Recently, some researchers have reported that zero-group-velocity (ZGV) Lamb waves have the potential to characterize properties of a layered media [3][4][5]. ZGV Lamb waves can reveal the elastic properties of anisotropic materials and thickness of a very thin surface layer with high accuracy and high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, when applied to structure health monitoring (SHM), wireless ultrasonic inspection has extensively been conducted for defect detection and thickness monitoring [1,2]. Conventional ultrasonic probes based on piezoelectricity were susceptible to technical problems such as electromagnetic interference and a lack of multiplexing capacity [3].…”
Section: Introductionmentioning
confidence: 99%